2022
DOI: 10.1155/2022/6098799
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Observation of Curative Effect of Trimetazidine Combined with Metoprolol in Elderly Patients with Coronary Heart Disease Complicated with Heart Failure and the Effect of Myocardial Remodeling by Integrated Traditional Chinese and Western Medicine

Abstract: Diabetic retinopathy (DR) is the most common complication of diabetes and is often characterized by damage to retinal vascular microcirculation, resulting in retinal exudation, hemorrhage, fibrosis, and neovascularization. With the aging of my country’s population, the incidence of DR is increasing year by year, and it has become one of the main blinding eye diseases in ophthalmic diseases also tends to be younger. So far, although the pathogenesis of DR is not completely clear, scholars generally believe that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[6] selected RN17, BL15 (bilateral), BL13 (bilateral), and BL17 (bilateral) to treat HF by moxibustion. Similarly, Ji et al [7] demonstrated that moxibustion can reduce serum high-sensitivity C-reactive protein (hs-CRP) and N-terminal precursor brain natriuretic peptide (NT-proBNP) levels in patients with chronic heart failure (CHF), and improve the clinical symptoms and cardiac function. The research of our research group also con rmed that moxibustion has a benign regulatory effect on heart and neuroendocrine function of CHF rats [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[6] selected RN17, BL15 (bilateral), BL13 (bilateral), and BL17 (bilateral) to treat HF by moxibustion. Similarly, Ji et al [7] demonstrated that moxibustion can reduce serum high-sensitivity C-reactive protein (hs-CRP) and N-terminal precursor brain natriuretic peptide (NT-proBNP) levels in patients with chronic heart failure (CHF), and improve the clinical symptoms and cardiac function. The research of our research group also con rmed that moxibustion has a benign regulatory effect on heart and neuroendocrine function of CHF rats [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the treatment methods for CHD combined with HLP mainly focus on reducing myocardial oxygen consumption [ 5 ] and improving myocardial blood circulation [ 6 ] while lowering blood lipid levels. Statins can stabilize vascular plaques, improve the function of endothelial cells, and most importantly, lower blood lipid levels by blocking the metabolic pathway of intracellular hydroxymethylglutaryl-coenzyme A and inhibiting cholesterol synthesis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine alone or combined with modern medicine strategies can increase the success rate of cardiovascular disease treatment. [ 12 ] It is necessary to explore the potential biomarkers and molecular mechanisms related to the occurrence and development of HF to provide more targeted and effective treatment strategies for patients and bring benefits. [ 13 ] Bioinformatics is a hybrid science that stores biological information by means of a combination of biological and technical data and plays a massive role in gaining extremely significant information on disorders that is useful in treatment development.…”
Section: Introductionmentioning
confidence: 99%